Sustainable development: Theory and some simple simulations - Alatorre, Jose Eduardo; Porcile, Gabriel; Sossdorf, Fernando; Torres, Miguel (PSL Quarterly Review, 2025)
This paper develops a unified framework to analyze the environmental, social, and economic dimensions of sustainable development within the context of a center-periphery international system. It introduces a three-gap model to address the challenges posed by the discrepancies among three key growth rates: the maximum growth rate compatible with external equilibrium, the minimum growth rate required for social inclusion, and the maximum growth rate consistent with environmental sustainability. Using updated theoretical and empirical insights, the paper applies the model to Latin American economies, highlighting the structural constraints and opportunities for achieving sustainable development in peripheral regions. By quantifying the interactions between technological capabilities, green investments, and social inclusion policies, the study offers policy recommendations to foster balanced and inclusive growth paths aligned with global sustainability commitments.